Resistant depression: criteria for determination, risk factors and therapeutic strategies - Khaustova, Olena (Psychosomatic Medicine and General Practice, 2017)
Background. Therapy of resistant depression raises a number of diagnostic and therapeutic problems, requires the solution of a number of methodological issues. A scientific discussion continues around the definition of depression resistance, assessment of the degree of reduction of depressive symptoms, the level of social and role functioning of patients; the improvement of models for determining the degree of resistance to various types of depression therapy continues; new methods of therapy and new algorithms of combined therapy are being developed. The ultimate goal of all these efforts should be practical recommendations for determining therapeutic options for the treatment of patients with resistant depression, which will help doctors make informed decisions on intervention strategies. Aim. To analyze the therapeutic possibilities of treating depressive disorders that are resistant to therapy. Methods. Publications from the Pubmed, MEDLINE, the Cochrane Library, Web of Science, Google Scholar databases were analyzed. Tags: depression, treatment, resistance, psevdoresistence, therapeutic response, resistance to treatment, strategies for treatment of resistant depression. Results. The terminology related to resistant depression was defined: lack of a therapeutic response, adequate dose, adequate duration of treatment, antidepressant intolerance, pseudo-resistance, relative resistance to treatment, absolute resistance to treatment, treatment of resistant depression, remission, recovery. Models for determining the resistance of depression have been described: the Thase & Rush model; European stepped model; A step model of the Massachusetts hospital; Step model of Maudsley; Form of the history of treatment with antidepressants. Risk factors for treatment of resistant depression were identified, and the main therapeutic strategies were described: optimization, switching, augmentation, combination and non-drug therapy. Particular attention is paid to the use of atypical antipsychotics as the augmentation strategy. A complex approach is described, which includes various combinations of the above strategies. Conclusion. Each case of treatment-resistant depression has its own unique characteristics and requires careful evaluation to determine the correct diagnosis and the quality of the therapeutic response. Equally important for building an adequate treatment plan is evaluating risk factors for the treatment of resistant depression. There is a wide variety of options for the treatment of resistant depression, so each therapeutic strategy should be used to help patients with treatment-resistant depression. The combination of antidepressant therapy and atypical antipsychotics with antidepressant properties in combination with psychotherapeutic intervention and adherence to adequate doses and duration of treatment may be a choice strategy for patients with treatment-resistant depression.